THE CULTURE OF TOLERANCE IN THE SHORT FILM "WEI" - Rifaqi, Dela Aufa; Adiprabowo, Vani Dias (Jurnal Kajian Seni, 2024)
"Wei" is a family-style short film released in 2020. This research will discuss religious tolerance in diverse societies like Indonesia. The film "WEI" is the subject of research that describes the values of religious tolerance through family relations in the film story. This research aims to know the meaning of tolerance in this film. The method used is narrative analysis; this film will identify the meaning, character development, and tolerance values in the story's beginning, middle, and end. The values of tolerance include recognition of family rights and mutual understanding between the film characters. This film illustrates that religious tolerance can grow through the appreciation of individual rights and understanding between different religious beliefs. This study concludes that tolerance is essential in social life, especially in the family, because tolerance itself is one of the reasons for the harmony of families with differences or religious convictions. As a family film, this film differs from some family films in Indonesia, where the main character, from the beginning to the end, has no dialogue. Still, the expression and character can explain the character's purpose to the audience in the film; this is the distinction between the Film Wei and the other family films.